Analysis of the efficiency and effectiveness of the use of budgetary funds - Kuttybaeva, N.; Raimbekov, B.; Temirbayeva, D.; Zhakina, G.E.; Rakhimova , A. (BUKETOV BUSINESS REVIEW, 2023)
Object: to show methods of effective use of budgetary funds and compare budget volumes in the field of the state budget Methods: during the research, various methods and techniques were used in the work: analysis, comparison, comparative evaluation of data, review, description, description of data. During the data analysis, the volume of the budget of the Republic of Kazakhstan for different years was obtained, as well as an analysis of the efficiency and effectiveness of the use of budget funds in general was carried out. Findings: general issues were considered in the article. The basic concepts are defined, the statistical deficit of the state budget is demonstrated and a methodology in the form of a figure is proposed in order to assess the effective spending of the state budget. Conclusions: The budget is not just funds, it can be called the backbone of the country. Only by regulating the full receipts and expenditures to the budget can the size of the deficit be adjusted annually. Tax revenues to the budget also do not fully affect the deficit. Therefore, for the correctness of receipts and expenditures, it is necessary to revise the budget system.